2005
DOI: 10.1271/bbb.69.1603
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical in the Edible Tamogi-take Mushroom (Pleurotus cornucopiae),D-Mannitol, Inhibits ACE Activity and Lowers the Blood Pressure of Spontaneously Hypertensive Rats

Abstract: D-Mannitol, one of the main phytochemicals of the edible Tamogi-take mushroom (Pleurotus cornucopiae), was found to inhibit an angiotensin I converting enzyme (ACE). The antihypertensive effect of D-mannitol and a hot water extract of Tamogi-take mushroom was demonstrated in spontaneously hypertensive rats (SHR) by oral administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Relatively high levels of linoleic acid, trehalose, and, particularly, of mannitol that are characteristic for S. subtomentosum might also be valuable considering renewed interests in (un)saturated fatty acids as modulators of lipid metabolism [25] and soluble saccharides as cryptobiotic substances [26] with a potential for treatment of serpinopathies [27] and Huntingtons disease [28]. Mannitol, one of the main phytochemicals of S. subtomentosum, has been claimed to protect against oxidation by hydroxyl radicals, confer protection against the development of colon cancer [29], inhibit ACE activity, and lower the blood pressure of hypersensitive rats [30].…”
Section: Results Andmentioning
confidence: 99%
“…Relatively high levels of linoleic acid, trehalose, and, particularly, of mannitol that are characteristic for S. subtomentosum might also be valuable considering renewed interests in (un)saturated fatty acids as modulators of lipid metabolism [25] and soluble saccharides as cryptobiotic substances [26] with a potential for treatment of serpinopathies [27] and Huntingtons disease [28]. Mannitol, one of the main phytochemicals of S. subtomentosum, has been claimed to protect against oxidation by hydroxyl radicals, confer protection against the development of colon cancer [29], inhibit ACE activity, and lower the blood pressure of hypersensitive rats [30].…”
Section: Results Andmentioning
confidence: 99%
“…7) Eritadenin isolated from Lentinula edodes has been reported to lower serum cholesterol levels. [9][10][11][12] More recently, hypotensive and hypoglycemic effects have been reported for the aqueous extracts of Pleurotus cornucopiae 13) and methanol-extracts of Hericum erinaceum, 14) respectively. It is also reported that polysaccharide from Inonotus obliquus has immune stimulation activity.…”
mentioning
confidence: 99%
“…Chemical modification and spectral analysis of reaction product were useful in establishing the structure of Compound 5. The compounds isolated from the leaves of P. crassipes were identified as ß-sitosterol C 29 H 50 O (1) (Lee et al 2003), ursolic acid (2) C 30 H 48 O 3 (Seebacher et al 2003), methyl chlorogenate C 17 H 20 O 9 (3) (Lee et al 2010), ethyl chlorogenate C 18 H 22 O 9 (4) (Lee et al 2010), rutin C 27 H 30 O 16 (5) (Lallemand & Duteil 1977, Bello et al 2011) and mannitol C 6 H 12 O 6 (6) (Hagiwara et al 2005). Quercetin C 15 H 10 O 7 (5a), the hydrolyzed product of rutin, was also identified (Lallemand & Duteil 1977).…”
Section: Resultsmentioning
confidence: 99%